2005
DOI: 10.1161/01.str.0000177866.13451.e4
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Disease Is an Independent Risk Factor for Stroke

Abstract: Background and Purpose-Chagas disease (CD) is frequently associated with cardioembolic stroke in South America. Our objective was to identify the predictors of stroke in a region where CD is endemic. Method-We screened 305 consecutive cardiopathy patients. Significant predictors of stroke in univariable analyses were included in a multivariable model. Results-Stroke was more frequent in CD (15.0%) compared with other cardiopathies (6.3%; Pϭ0.015). Other predictors of stroke in univariable analyses were previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 13 publications
(11 reference statements)
2
29
2
1
Order By: Relevance
“…This reaffirms the strong association of this disease with cerebrovascular pathologies, as already determined by previous studies 4,5,6,7,8 . In this sample, non-valvular atrial fibrillation was 40% less frequent in patients with CIS, probably because the most frequent indication for anticoagulation in patients without prior CIS is atrial fibrillation itself.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This reaffirms the strong association of this disease with cerebrovascular pathologies, as already determined by previous studies 4,5,6,7,8 . In this sample, non-valvular atrial fibrillation was 40% less frequent in patients with CIS, probably because the most frequent indication for anticoagulation in patients without prior CIS is atrial fibrillation itself.…”
Section: Discussionsupporting
confidence: 90%
“…This sample comprised only patients with CDCM, limiting any analysis regarding patients with Chagas disease but without cardiac manifestations. It has been shown that, even in patients without cardiac abnormalities, a confirmed Chagas disease positive serology increases the risk of ischemic stroke 5,6,7 . This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of right HF, such as edema, increased abdominal volume and epigastric discomfort, can appear early, but are more frequent at advanced stages of disease, accompanied by low cardiac output symptoms, such as intolerance to exertion. Suggestive history of arrhythmic events (bradyarrhythmia or tachyarrhythmia) with palpitations, presyncope and syncope is frequent 79,84,85 . Thromboembolic events, mainly CVA, can be the first manifestation of CCC, and originates mainly from intracavitary thrombi 84 .…”
Section: Cardiac Form With Ventricular Dysfunctionmentioning
confidence: 99%
“…Suggestive history of arrhythmic events (bradyarrhythmia or tachyarrhythmia) with palpitations, presyncope and syncope is frequent 79,84,85 . Thromboembolic events, mainly CVA, can be the first manifestation of CCC, and originates mainly from intracavitary thrombi 84 . Angina of atypical character is frequent, results from ischemia in the absence of angiographically detectable coronary obstruction, and is explained by inflammatory changes, thrombosis and other coronary microcirculation disorders 32,37,75 .…”
Section: Cardiac Form With Ventricular Dysfunctionmentioning
confidence: 99%
“…In the chronic phase, cerebrovascular disease is a recognized cardioembolic complication in patients with Chagas' disease even in the absence of cardiomyopathy or cardiac arrhythmias 2 . other stroke mechanisms are described with some authors suggesting an association between Trypanosome infection itself and stroke 3 . other authors suggest that au-Chagas' disease: antiautonomic antibodies Py et al tonomic dysfunction might be responsible for cerebrovascular disease as it may induce endothelial dysfunction leading to vasoconstriction, cerebral vascular spasms and, ultimately, a clinically defined stroke 4 .…”
mentioning
confidence: 99%